An Exploration of Smoking Among People Attending Residential Substance Abuse Treatment: Prevalence and Outcomes at Three Months Post-Discharge. Issue 1 (2nd January 2017) - Ingram, Isabella; Kelly, Peter J.; Deane, Frank P.; Baker, Amanda L.; Lyons, Geoff; Blackman, Russell
ABSTRACT: Objectives : Smoking continues to be a major health concern for people with a history of alcohol or other substance use problems. The current research is aimed to (1) describe the prevalence of smoking in residential addictions treatment services and (2) compare characteristics of people who had or had not quit smoking.Methods : Participants were attending residential substance abuse treatment provided by the Australian Salvation Army. These programs are up to 10 months in length and offer a range of low-intensity smoking cessation supports. Measures of smoking, substance use, and clinical characteristics were collected from 2008 to 2015 at baseline and three months post-discharge from treatment ( N = 702).Results : At baseline, 86% of people were smokers ( n = 606). At follow-up, only 48 participants who were smokers at baseline (7%) had quit smoking. Participants who had quit smoking at follow-up also reported higher rates of abstinence from alcohol or other substances at follow-up (72%) than people who had not quit smoking (46%; OR = 2.95, 95% CI [1.52, 5.74]).Conclusions : There is potential for smoking cessation to be better addressed as part of routine care in substance abuse treatment settings. Future research should evaluate the provision of more systematic smoking cessation interventions within these settings.